Narrative Inquiry: A Critical Examination of Its Theoretical Foundations and Methodological Applications - Chand , Gambir Bahadur (Far Western Review, 2024)
This review article offers an in-depth examination of narrative inquiry, a methodological approach dedicated to exploring individual stories to gain insights into their experiences. The article begins by introducing narrative inquiry, elucidating its origins, significance, and applicability across various disciplines. It then explores narrative inquiry as a research design, highlighting its capacity to facilitate an in-depth exploration of personal and social narratives. The review proceeds to outline the procedural steps involved in conducting narrative research, encompassing the formulation of research questions, data collection, and the interpretation of narrative data. Following this, the article details the methods for data analysis within narrative inquiry, emphasizing the critical roles of contextual and thematic analysis in revealing underlying meanings. The discussion concludes with an examination of ethical considerations pertinent to narrative inquiry, emphasizing the importance of maintaining confidentiality and privacy for participants. Through this comprehensive review, the article aims to furnish researchers and scholars with a robust understanding of narrative inquiry, including its methodological underpinnings and practical applications.